A Meta-analysis into the Effectiveness of Doctoral Dissertations on Constructivist Learning - Erisen, Yavuz; Gunay, Rafet (KAMLA-RAJ ENTERPRISES, 2015)
This paper aims to combine the results obtained by studies conducted independently of each other on constructivist learning in Turkey. The question the study seeks to answer is expressed as: Does constructivist learning approach affect students' academic achievement?. In this context, the literature research was made between 2001 and 2013, and 27 doctoral dissertations written in Turkish about the effect of constructivist learning on students academic achievement were included in the meta-analysis. In line with the determined criteria, the 27 doctoral dissertations conducted on the effect of constructivist learning in Turkey, it can be said that the applied constructivist education has an effect on academic achievement in the classification framework of Cohen and it is located in the wide interval which is the highest level. Following meta-analysis, it was concluded that constructivist learning approach was effective in terms of academic achievement in the positive direction.
Keywords: Academic Achievement,Effect Size; Level of Schooling; Random-effects Model; Type of Subject; SELF-EFFICACY BELIEFS; POWER; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics